Christian Approaches to International Affairs - Troy, Jodok (Palgrave Macmillan, 2012)
Troy analyses how the understanding of religion in Realism and the English School helps in working towards the greater good in international relations, studying religion within the overall framework of international affairs and the field of peace studies